Would a Placebo Acupuncture Needle be Able to Induce Deqi? - Cássia Maria Grillo; Vera Lúcia Rasera Zotelli; Maria Lúcia Bressiani Gil; Maria da Luz Rosário de Sousa (Medical Association of Pharmacopuncture Institute, 2018)
The aim of this study was to evaluate Deqi in patients under treatment with acupuncture and sham acupuncture. Forty (40) volunteers of all genders with temporomandibular dysfunction (TMD) were randomized into two study groups: Acupuncture and Sham Acupuncture (non-penetrating device). The patients answered the Southampton Needle Sensation Questionnaire (SNSQ) at the initial and final sessions of acupuncture treatment. The questionnaire was composed of two parts: the first one, consisting of 17 Deqi descriptors and a Likert scale in order to evaluate the intensity of each sensation; and the second one, consisting of a visual analog scale (VAS) to evaluate how painful the acupuncture treatment was. At the initial session, LI4 was the most cited acupuncture point in both groups, being responsible for a 'Slight Intensity' needling sensation of electric shock in the acupuncture group at initial (10%) and final (15%) sessions. The most common related needling sensations at different acupuncture points was "Pricking" and "Sharp" in both groups. The acupuncture group showed higher VAS than the Sham Acupuncture either in the initial (3.87 × 2.43) and final (2.04 × 2.14) sessions. Deqi response to acupuncture stimulation was verified either in the both groups. Keywords: Acupuncture points, Deqi response, Placebo, Skin